The Faith on the Creation of Buddhist Art in Lanna - theerasuttapot, Ven. Phrakru (Journal of International Buddhist Studies, 2015)
According to the term ‘Saddhā’. It refers to faith; belief; confidence associated with emotion. To the faith in the Buddhist Arts, it aims to attract the people to venerate the Buddhism that existed from the fourfold ofjudge or take standard viz., Råpa-pamàõa: the beauty of appearance or form, Ghosa-pamàõa: faith depends on sweet voice or good reputation, Låkha-pamàõa: faith depends on shabbiness or ascetic or selfdenying practices and Dhammapamàõa: faith depends on right teachings and practices. The above mentioned not only resulted or caused the confidence to people, but also develop knowledge of the worldly person. The beauty of arts produces the aesthetic feelings and also the confidence in the Enlightenment of the Buddha in the form of Uddesikacetiya i.e. a Buddha image. Regarding to the development of the Buddhist Arts in Lanna region, it has been existed and shared the similarities with the Dvaravati architecture and the Burmese arts in Bagan style. There are some characteristics that unique to the folk artisans which later it has developed as the prototype of Lanna architecture around the 20th century. The highest development of Lanna arts existed around the 20th century and the Chiang Mai Kingdom becomes the centre of Buddhism. The works of arts were considered to be strongly related to the propagation of Lankavamsa Buddhism. The Lanna Buddhist Arts represent the wide range of forms that were inspired by architecture in the previous period viz., Sukhothai, Burma in Bagan period, etc. It was seamlessly developed with the vernacular architecture and has been passed down for generations with the confidence of creating the Buddhist arts in Lanna. In case of building a temple, not only the kings, but also the ordinary people can be the president of construction. Regarding to Wat Mahawan in Chiang Mai and WatChedi Saw in Lampang they were appearing in the Burmese arts, Wat Srisuphan and Wat BuakKrokLuang appeared in the form of Tai Khuen Arts. There were some temples have been built by the group of artists or folks artisans viz., Wat Phuak Tam. Therefore, it can be seen that the Lanna Buddhist Arts consisted with the variety of art forms with the beauty that characterized by the Lanna people.